Neuropeptide Y, resilience, and PTSD therapeutics. (10th May 2017) - Kautz, Marin; Charney, Dennis S.; Murrough, James W.
Abstract: Resilience to traumatic stress is a complex psychobiological process that protects individuals from developing posttraumatic stress disorder (PTSD) or other untoward consequences of exposure to extreme stress, including depression. Progress in translational research points toward the neuropeptide Y (NPY) system − among others − as a key mediator of stress response and as a potential therapeutic focus for PTSD. Substantial preclinical evidence supports the role of NPY in the modulation of stress response and in the regulation of anxiety in animal models. Clinical studies testing the safety and efficacy of modulating the NPY system in humans, however, have lagged behind. In the current article, we review the evidence base for targeting the NPY system as a therapeutic approach in PTSD, and consider impediments and potential solutions to therapeutic development.